2022
DOI: 10.3390/life12081248
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking the ‘Asymptomatic’ COVID-19: A Nose Question

Abstract: The new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus has high infectivity, often masked by asymptomatic carriers, which allows it to spread rapidly and become a pandemic. Attempts to slow the pandemic at this stage depend on the ability to unmask asymptomatic carriers. The rapid diagnosis of active coronavirus disease 2019 (COVID-19) infection is one of the cornerstones of pandemic control, as the nasal cavity is the main gateway for SARS-CoV-2 entry and altered sense of smell is a featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…In contrast, in our study population of healthcare workers, COVID-19 was confirmed in 4% of individuals in April–May 2020, and in June 2020, IgG class anti-SARS-CoV-2 antibodies were detected in over 7.5% of subjects. This seems to confirm the literature data, pointing to significant proportions of low symptomatic or asymptomatic cases or cases with atypical symptoms among people with COVID-19 who spread the infection easily and unnoticed [ 43 ]. The large proportion of asymptomatic cases significantly biased both the perception of the real extent of SARS-CoV-2 circulation in the Polish population and estimations of the infection/fatality ratio [ 44 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, in our study population of healthcare workers, COVID-19 was confirmed in 4% of individuals in April–May 2020, and in June 2020, IgG class anti-SARS-CoV-2 antibodies were detected in over 7.5% of subjects. This seems to confirm the literature data, pointing to significant proportions of low symptomatic or asymptomatic cases or cases with atypical symptoms among people with COVID-19 who spread the infection easily and unnoticed [ 43 ]. The large proportion of asymptomatic cases significantly biased both the perception of the real extent of SARS-CoV-2 circulation in the Polish population and estimations of the infection/fatality ratio [ 44 ].…”
Section: Discussionsupporting
confidence: 90%
“…This finding confirms the importance of the problem of the people, often called non-responders [ 46 , 47 ], who do not produce antibodies after contact with SARS-CoV-2 antigens. Alternatively, this may be explained by a rapid decrease in initially achieved antibody levels to values below lab detection limits in a significant percentage of the population [ 43 ]. The ability of the immune system to protect against a severe course of the disease and the response of these people to standard COVID-19 vaccinations remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The reviews by Scotto et al [60] and Pang et al [61] analyze the correlations between taste alterations and SARS-CoV-2 establishing the diagnostic value of this chemosensitive disorder. The diagnostic value of olfactory disorders is instead the subject of studies by Mazzatenta et al [62,63] and Jungbauer et al [64].…”
mentioning
confidence: 99%